Al-Farabi and word culture in Eurasian context - Saduov, A.Zh.; Makulbekov, A.T.; Malikova, A.M.; Rakimzhanova, S.K. (KU Publ., 2021)
The article analyzes the life and work of Al-Farabi within the context of Eurasian Geography and contemporary realities. The legacy of Al-Farabi is a source of inspiration, knowledge, and solutions to many present problems, since his writings bring together the wisdom of the East and the progressive approach of the West. The multi-faceted nature and relevance of tractates of the Second Teacher can be used as a practical tool for the development of the people of Kazakhstan and improvement of the spiritual component of a personality and a community.
Әл-Фараби және Еуразиялық кеңістіктегі әлемдік мәдениет
Аль-Фараби и мировая культура в Евразийском пространстве
Keywords: Al-Farabi; world culture; oriental philosophy; Eurasian space; great steppe